Age, weight and ovulation rate of puberty of hairy sheep of Northeast Brazil - Silva, Antonio Emídio Dias Feliciano; Nunes, José Ferreira; Riera, Gerardo Simon; Foote, Waren C. (Pesquisa Agropecuaria Brasileira, 2014)
In 72 Morada Nova, Santa Inês and Brazilian Somalis, hairy-breed ewes were determined weight, age and ovulation rate at puberty by means of ovarian endoscopy. The ewes were submitted to endoscopy examination sixty hours after teasing with vasectomized rams. The ewes were divided in two groups, G I and G II, 36 each, and alloted to two treatments as follows: native pasture and confinement. These groups were again arranged in a factorial design (3 x 2 x 2) according to the breeds, type of birth and nutritional management. In the pasture, the age and weight at puberty of Morada Nova, Somalis and Santa Inês breeds were, respectively, 306.9, 346.4 and 360.4 days and, 23.2 kg, 19.3 kg and 27.1 kg; on the other hand, showing in confinement, 250.7, 268.4 and 277.8 days and, 23.8 kg, 23.7 kg and 34.2 kg. The age (P <0.05) and weight (P <0.001) at puberty were affected by nutritional management in the three breeds. The difference ovulation rate was not significant in comparison between groups. The Morada Nova breed exhibited the best physiological adaptation to native pasture, in precocity and ovulation rate. The hairy sheep of Northeast Brazil showed the first estrus (puberty) at around one year of age and with a weight equivalent to 60% to 70% of the adult weight for each breed.